2015
DOI: 10.1111/evo.12697
|View full text |Cite|
|
Sign up to set email alerts
|

Reproduction alters oxidative status when it is traded-off against longevity

Abstract: Oxidative stress has been proposed to mediate one of the most important aspects of life-history evolution: the trade-off between reproduction and self-maintenance. However, empirical studies have cast doubt on the generality of this intriguing notion. Here, we hypothesize that reproduction alters oxidative status only when a trade-off between reproduction and self-maintenance occurs. Accordingly, in female Bicyclus anynana butterflies, we found that reproduction affected oxidative markers only under challengin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…Moreover, a trade-off was observed between self-maintenance and reproduction in animals. The effects of such a trade-off on the oxidative status depend on whether priority is given to self-maintenance or reproduction33. Accordingly, the development and reproduction of T. cinnabarinus feeding on the transgenic cassava lines were significantly inhibited in this study (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 65%
“…Moreover, a trade-off was observed between self-maintenance and reproduction in animals. The effects of such a trade-off on the oxidative status depend on whether priority is given to self-maintenance or reproduction33. Accordingly, the development and reproduction of T. cinnabarinus feeding on the transgenic cassava lines were significantly inhibited in this study (Figs 5 and 6).…”
Section: Discussionmentioning
confidence: 65%
“…We then measured ADH activity and the oxidative status of butterflies by following protocols described in Fischer et al (2014) and Beaulieu et al (2015). Briefly, the frozen body (thorax and abdomen) of each butterfly was crushed in 200 μl of phosphatebuffered saline (100 mmol l −1 , pH 7.4) with one tungsten carbide bead (3 mm) at high speed shaking (30 times s −1 , 1 min).…”
Section: Fitness and Physiological Parametersmentioning
confidence: 99%
“…Studies on vertebrates have examined the relationship between SSC and the levels of ROS and antioxidant production, as well as damage to biomolecules (Metcalfe & Monaghan, ; Monaghan, Metcalfe, & Torres, ; Sharick, Vazquez‐Medina, Ortiz, & Crocker, ). With regard to invertebrates, however, studies of oxidative stress have considered traits such as predation (Janssens & Stoks, ), reproduction (Rey, Pélisson, Bel‐Venner, Voituron, & Venner, ) and sexual dimorphism in life span and ageing (Archer, Sakaluk, Selman, Royle, & Hunt, ; Beaulieu, Geiger, Reim, Zielke, & Fischer, ). The authors of a key paper found that younger males of the cricket Gryllodes sigillatus had more total antioxidant capacity (TAC) than older males and suggested that calling effort may increase pro‐oxidants, favouring a decrease in oxidative stress defences (Archer et al., ).…”
Section: Introductionmentioning
confidence: 99%